Metamorphoses : in Rodin's studio - Bondil, Nathalie; Biass-Fabiani, Sophie; Rodin, Auguste, 1840-1917.; Musée des beaux-arts de Montréal; Virginia Museum of Fine Arts; Peabody Essex Museum (Montreal : Museum of Fine Arts, 2015)
Metamorphoses: in Rodin's studio reveals the work of Auguste Rodin (1840-1917) and the materials he used to accomplish it, along with his collaborators, models, studio assistants and founders, as observed by eyewitnesses, photographers and writers. The theme of metamorphosis plunges us directly into the secrets of the studio to unveil the constantly shifting creative process of this revolutionary sculptor. Rodin is a pivotal figure not only because of his expression, of a rare emotional and psychological complexity, but also because of his profound renewal of the language of sculptural practice. One of the most striking aspects of his vision lies in his ascribing greater value to the act of creation, which he placed in the forefront, than to the imperious dogma of a necessarily completed work: no sculpture was ever immutably final in Rodin's mind.
Rodin: Metamorphoses / Sophie Biass-Fabiani -- Rodin's world of plaster / Catherine Chevillot -- "In the studio of the world ..." / Véronique Mattiussi -- Reassembled profiles of Rodin's method: "understanding is a long and difficult process" / Nathalie Bondil -- When Rodin would write on his works / Sophie Biass-Fabiani -- Rodin and his models: comedy or curtain-up / Hélène Pinet -- The photographers: Eugène Druet and Pierre Choumoff / Hélène Pinet -- Breathing life into stone: Rodin and his marble statues / François Blanchetière -- Rodin's bronze sculpture: capturing his vision, perpetuating his legacy / Daphne Barbour and Lisha Deming Glinsman -- Max Stern's Rodin bronzes: a Montreal story / Sylvain Cordier -- The burghers of Vancouver: interview with Denys Arcand and Adad Hannah / Catherine Bédard -- Anthology. Truman Howe Bartlett: "Auguste Rodin", The American architect and building news, vol. XXV, no. I-X, January-June 1889 / introduction by Sophie Biass-Fabiani -- Visits to the studio / texts collected and introduced by Sophie Biass-Fabiani.
Catalogue accompanies the exhibition held at the Montreal Museum of Fine Arts, May 30-October 18, 2015, Virginia Museum of Fine Arts, Richmond, November 21, 2015-March 13, 2016, Peabody Essex Museum, Salem, May 16-September 5, 2016.
Published also in French under the title: Métamorphoses : dans l'atelier de Rodin.
Some essays translated from French.
boek
Keywords: Rodin, Auguste, -- 1840-1917 -- Exhibitions; Sculpture, French -- 19th century -- Exhibitions; Sculpture, French -- 20th century -- Exhibitions; Sculpture -- Technique -- Exhibitions